El Excentrico, 1960-06-05 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
June 05, 1960 [5 de junio de 1960]. Ano 10, No 18. Cover has a photograph of newly married couple exiting the wedding cermony as guest throw rice in celebration. The headline reads, "The former Myrna Lee Gary exchanged vows with Bill Proctor."